A Comprehensive Review of the Integration of Physiotherapy, Nursing, Assistant Nursing, X-Ray and Health Informatics in Modern Healthcare - A lasloom , Awad saleh; A lasloom , Mohammed saleh; A Alduways , Mohammed Hassan; Alduways , Rashed Ali; Alyami , Hussain Ali Hussain; Alazmi , Saed Hamdan S; Alanazi , Eman Suwayyid H; Alsharari , Obaidallah Mohammed S; Alsharari , Aihmad Muflih M; AlSharari , Abdullah Mufleh M; Alsharari , Madallah Lafi M; Alazmi, Nimah Naif Alaswad; et al. (Journal of Ecohumanism, 2024)
It is necessary to integrate different healthcare specialties to assure high quality of patient-centred care. This review contains physiotherapy, nursing, assistant nursing, X-ray, and health informatics roles in the modern health care system regarding their collaborated effect on patient outcomes. This paper uses existing literature to look at how interdisciplinary collaboration is a more efficient, less costly, and better way to care for patients. However, these challenges of integration can be overcome and the many benefits can be harnessed, including improved clinical decision support and streamlined workflow. The final section of the review recommends policies that enhance integration, training the workforce for these changes, and the integration of advanced health informatics systems.